(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The globalization of clinical trials has become increasingly prevalent in recent years, driven by factors such as access to diverse patient populations, cost efficiencies, and faster recruitment timelines. This article provides a comprehensive overview of the opportunities and ethical considerations associated with conducting clinical trials on a global scale. It explores the benefits of globalizing clinical research, including enhanced recruitment capabilities, broader generalizability of results, and accelerated drug development processes. However, it also addresses the ethical complexities inherent in this practice, such as ensuring adequate informed consent, protecting the rights and welfare of participants, and addressing disparities in healthcare infrastructure and standards of care across different regions. By examining both the opportunities and challenges, this article aims to inform stakeholders involved in the planning, execution, and oversight of global clinical trials.